COMPARATIVE ANALYSIS OF DOMESTIC AND FOREIGN EXPERIENCE IN PERSONNEL ADAPTATION - R. Esikova; N. Vyzhimova (Вестник Северо-Кавказского федерального университета, 2022)
The article is devoted to the peculiarities of the process of personnel adaptation in organizations taking into account domestic and foreign experience. In today's business environment, personnel is one of the key factors that determine the company's success. The main task for Russian companies is to use positive foreign experience, trying to change it to suit Russian conditions, taking into account the mentality and specifics of their activities. Only then will it be possible to fix adaptation as one of the important functions of personnel management.